Health Impacts of Climate Change in the Solomon Islands: An Assessment and Adaptation Action Plan - Spickett, Jeffery; Katscherian, Dianne (Canadian Center of Science and Education, 2014)
The Pacific island countries are particularly vulnerable to the environmental changes wrought by global climate change such as sea level rise, more frequent and intense extreme weather events and increasing temperatures. The potential biophysical changes likely to affect these countries have been identified and it is important that consideration be given to the implications of these changes on the health of their citizens.The potential health impacts of climatic changes on the population of the Solomon Islands were assessed through the use of a Health Impact Assessment framework. The process used a collaborative and consultative approach with local experts to identify the impacts to health that could arise from local environmental changes, considered the risks associated with these and proposed appropriate potential adaptive responses. Participants included knowledgeable representatives from the biophysical, socio-economic, infrastructure, environmental diseases and food sectors.The risk assessments considered both the likelihood and consequences of the health impacts occurring using a qualitative process. To mitigate the adverse effects of the health impacts, an extensive range of potential adaptation strategies were developed. The overall process provided an approach that could be used for further assessments as well as an extensive range of responses which could be used by sectors and to assist future decision making associated with the Solomon Islands’ responses to climate change.